1982
DOI: 10.1111/j.1423-0410.1982.tb00006.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment by Plasma Exchange of a Patient with Hyperlipidemia and Diabetic Ketoacidosis with Lesional Pulmonary Edema and Acute Pancreatitis

Abstract: The authors report a case of severe hypertriglyceridemia (148.5 mmol/l) in a 27-year-old woman admitted for coma of unknown origin. Initial investigations revealed ketoacidosis, pancreatitis and noncardiogenic pulmonary edema. The diabetes was unknown. Ketoacidosis was rapidly controlled. The hypertriglyceridemia was corrected by one course of plasma exchange (4,400 ml) during which the patient returned to consciousness. The patient recovered without any sequelae. Only 2 similar cases, treated by plasma exchan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

1984
1984
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 8 publications
(2 reference statements)
0
6
0
1
Order By: Relevance
“…Although the published experiences with plasma exchange in hyperlipidemic pancreatitis are scanty, the available reports suggest that it is effective for ischemic heart failure with hypercholesterolemia ( Thompson et al 1980) and for diabetic ketoacidosis with hypertriglyceridemia (Gerard et al 1982). We have demonstrated in both experimental and clinical studies that plasma exchange, accounting for five percent of the body weight, could reduce the high pancreatic enzyme levels down to about 50% (Yamauchi et al 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Although the published experiences with plasma exchange in hyperlipidemic pancreatitis are scanty, the available reports suggest that it is effective for ischemic heart failure with hypercholesterolemia ( Thompson et al 1980) and for diabetic ketoacidosis with hypertriglyceridemia (Gerard et al 1982). We have demonstrated in both experimental and clinical studies that plasma exchange, accounting for five percent of the body weight, could reduce the high pancreatic enzyme levels down to about 50% (Yamauchi et al 1985).…”
Section: Discussionmentioning
confidence: 99%
“…In 1.3-3.8% of the patients, the etiology of acute pancreatitis has been ascribed to severe primary and secondary hypertriglyceridemia [2] . In the 1980s, plasmapheresis was fi rst used to treat patients with severe acute hyperlipidemic pancreatitis with satisfying results [3] .…”
Section: Introductionmentioning
confidence: 99%
“…Plasmapheresis in hyperlipidemia is not routinely done 22 . Although not an established treatment for hypertriglyceridemia, plasmapheresis has been reported to be effective in critically ill patients, often leading to a good clinical outcome 23‐26 . Yeh and coworkers 27 showed that plasma exchange treatment is an effective method for clearing lipids and enzymes from the plasma of patients with severe hypertriglyceridemia who had not responded to previous therapies.…”
Section: Discussionmentioning
confidence: 99%